Analisis Persepsi Siswa terhadap Penggunaan Aplikasi Quizizz pada Materi Hidrokarbon - Sulasmi, Rahma; Mahartika, Ira (Asatiza: Jurnal Pendidikan, 2022)
Quizizz online learning application is one of the most widely used learning evaluation applications, especially during the covid-19 pandemic. This study aims to analyze students' perceptions of the use of Quizizz in chemistry subjects with Hydrocarbons Material. This study uses a quantitative method with a descriptive approach at Madrasah Aliyah Nurul Wathan Pasar Kembang. 36 students were selected by purposive sampling, the data were collected using a questionnaire technique, while the data were analyzed using descriptive analysis techniques. The results of the data analysis showed that students (89%) had a very good perception of the use of Quizizz in chemistry subjects with Hydrocarbon Materials.